2018
DOI: 10.7220/2345-024x.22.2
|View full text |Cite
|
Sign up to set email alerts
|

Examination of convergent validity of START: AV ratings among male juveniles on probation

Abstract: The Short-Term Assessment of Risk and Treatability: Adolescent Version (START: AV, Viljoen, Nicholls, Cruise, Desmarais, & Webster, 2014) provides a structural professional judgement on the risk of adverse outcomes related to harm to others and rule violations. The advantage of START: AV is in that it includes the assessment of both strengths and vulnerabilities. As it is a relatively new assessment tool, the questions related to psychometric properties of the measure are still topical, especially in intercult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 48 publications
4
12
4
1
Order By: Relevance
“…To our knowledge, this study was the first to assess the interrater reliability of the START:AV completed by professionals in a secure youth forensic mental health setting as part of their day‐to‐day responsibilities. Consistent with emerging research on field reliability, we found lower interrater reliability than studies that examined the START:AV for research purposes only (Klimukienė et al., 2018; Viljoen et al., 2012). We first discuss our findings in light of previous research, and then describe factors that could have contributed to these lower interrater reliability findings.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…To our knowledge, this study was the first to assess the interrater reliability of the START:AV completed by professionals in a secure youth forensic mental health setting as part of their day‐to‐day responsibilities. Consistent with emerging research on field reliability, we found lower interrater reliability than studies that examined the START:AV for research purposes only (Klimukienė et al., 2018; Viljoen et al., 2012). We first discuss our findings in light of previous research, and then describe factors that could have contributed to these lower interrater reliability findings.…”
Section: Discussionsupporting
confidence: 85%
“…The START:AV items are combined into overall ratings of “strengths” and “vulnerability,” and total scores for both can be calculated for research purposes. With half a dozen publications, research on the psychometric properties and utility of the START:AV is still in its infancy (Desmarais et al., 2012; Klimukienė et al, 2018; Sellers et al, 2017; Sher et al, 2017; Singh et al., 2014; Viljoen et al., 2012). Moreover, most of these studies have used the pilot version of the instrument.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iš pradžių adaptacijos pataisos įstaigoje tyrimai buvo vykdyti iš sociologinės perspektyvos, analizuojant, kaip nuteistieji asimiliuojasi su pataisos įstaigos kultūra, perima jos normas ir t. t. (Clemmer, 1950). Vėliau ilgą laiką tyrimuose adaptacija buvo vertinama pagal nuteistųjų pataisos įstaigoje padarytus nusižengimus, laikant, kad kuo daugiau režimo pažeidimų padarė nuteistasis, tuo jo adaptacija yra blogesnė (Holland & Holt, 1980;Harrington, 2012). Tačiau akivaizdu, kad vien daromi nusižengimai nepakankamai gerai atspindi tokį sudėtingą reiškinį kaip adaptacija pataisos įstaigoje.…”
Section: Adaptacijos Pataisos įStaigoje Teoriniai Modeliaiunclassified